(untitled) (Actualizaciones en Sida e Infectología, 2024)
Infection is the most common complication of cerebrospinal fluid (CSF) devices. The organisms adhere to the surface and form a biofilm, which difficults clinical diagnosis, laboratory and treatment. OBJECTIVES: Incidence of infection, isolated microorganisms, risk factors, reinfection rate and mortality in a neurosurgical reference hospital. MATERIAL AND METHODS: Retrospective, analytical, observational cohort study. Inclusion criteria: over 15 years old, with CSF devices: EVD and IVD. Period: From June 1, 2020 to June 1, 2022. p<0.05. Multivariate analysis was performed. Epi Info 7. RESULTS: 104 surgical procedures (57 patients); 62% men. Average age: 37 years. Reason for device placement: 57% ventricular hemorrhage, 43% brain trauma, 24% CSF fistula. 20% episodes of infection: 15% ventriculitis (incidence: 17.33/1000 device days) and 5% infections associated with IVD. Most frequent risk factors: CSF fistula (OR 4.75), ventricular hemorrhage (OR 3.65), device stay longer than 5 days (OR 3.76), device replacement (OR 2.76), DVP revision (OR 3.15). Most frequent germs methicillin resistant Staphylococcus epidermidis (19%) and MOMR 24%. Reinfection: 28%. Mortality 10%. CONCLUSION: Infection rate of 20% (reference values ​​according to the literature range from 0 to 22%). Limited reports from Argentina. Risk factors and mortality are similar to those reported in the literature. It is very important to implement prevention and intervention measures in order to minimize the risk of infection to reduce morbidity and mortality and the inappropriate use of antimicrobials. The knowledgement of local data is important.